Evaluation of different photoperiods in the larval culture of the bullseye puffer fish (Sphoeroides annulatus) - ´Abdo-de la Parra, María Isabel; Martínez-Chávez, Carlos Cristián; Rodríguez-Ibarra, Luz Estela; Rodríguez-Montes de Oca, Gustavo (Ecosistemas y Recursos Agropecuarios, 2023)
The objective of the present work was to evaluate the effect of different photoperiods on hatching, growth and survival of Sphoeroides annulatus larvae in order to improve the existing culture protocol. In each of the 12 fiberglass tanks, 5 g of degummed eggs were placed and the hatching rate, growth in total length, weight and survival of larvae were evaluated under four photoperiods with three replicates each: 24 hours light (hl), 18 hl, 12 hl and 0 hl, for 45 days after hatching. Hatch rate was significantly lower at 0 hl and larvae did not survive to 5 days after eclosion. Growth was significantly higher at 12 hl. Survival did not show significantdifferences between treatments. The results suggest that photoperiod affects the hatching rate and growth of S. annulatus larvae under the conditions ofthis study.
Keywords: Sphoeroides annulatus, photoperiod, hatch, larvae